2002
DOI: 10.1182/blood-2002-01-0101
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum cysteine protease falcipain-2 cleaves erythrocyte membrane skeletal proteins at late stages of parasite development

Abstract: Plasmodium falciparum-derived cysteine protease falcipain-2 cleaves host erythrocyte hemoglobin at acidic pH and specific components of the membrane skeleton at neutral pH. Analysis of stage-specific expression of these 2 proteolytic activities of falcipain-2 shows that hemoglobinhydrolyzing activity is maximum in early trophozoites and declines rapidly at late stages, whereas the membrane skeletal protein hydrolyzing activity is markedly increased at the late trophozoite and schizont stages. Among the erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 32 publications
2
73
0
Order By: Relevance
“…The S2 pocket is the major determinant of specificity for most cysteine proteases (66), and its predominantly hydrophobic nature in falcipain-2 agrees well with the observation that all characterized falcipain-2 cleavage motifs of its specific intracellular protein targets, including ankyrin (NVSAR2FWLSD) (67), band 4.1 (SQEEIK2KHHASI) (17), and the falcipain-2 precursor (KYLLD2QMNYF) (18), contain a hydrophobic residue at the P2 position (marked in bold in the preceding sequences). Experiments with fluorogenic substrates have also shown that falcipain-2 has a strong preference for substrates with a hydrophobic residue, particularly Leu, at the P2 position (18).…”
Section: Structural Determinants Of Protein Folding and Hemoglobinsupporting
confidence: 71%
See 1 more Smart Citation
“…The S2 pocket is the major determinant of specificity for most cysteine proteases (66), and its predominantly hydrophobic nature in falcipain-2 agrees well with the observation that all characterized falcipain-2 cleavage motifs of its specific intracellular protein targets, including ankyrin (NVSAR2FWLSD) (67), band 4.1 (SQEEIK2KHHASI) (17), and the falcipain-2 precursor (KYLLD2QMNYF) (18), contain a hydrophobic residue at the P2 position (marked in bold in the preceding sequences). Experiments with fluorogenic substrates have also shown that falcipain-2 has a strong preference for substrates with a hydrophobic residue, particularly Leu, at the P2 position (18).…”
Section: Structural Determinants Of Protein Folding and Hemoglobinsupporting
confidence: 71%
“…During the late trophozoite and schizont stages, falcipain-2 is also involved in the degradation of erythrocyte-membrane skeletal proteins including ankyrin and the band 4.1 protein (17). This activity displays a pH optimum in the range of 7.0 -7.5 and is thought to contribute to destabilization of the erythrocyte membrane, leading to host cell rupture and release of the mature merozoites.…”
mentioning
confidence: 99%
“…Identifying the proteases expressed in both the asexual and the sexual stages and their in vivo accessibilities to inhibitors is an important component of drug development. Previous work has implicated falcipains 2A/B and 3 in asexual hemoglobin digestion and, possibly, RBC emergence, and recombinant falcipains 2A and 3 have been used in a number of drug screening assays (6,7,11,29,31,33,34). The data from this study demonstrating that gametocytes express falcipain 3 and not falcipain 2A/B, coupled with the possibility that falcipain 3 could be essential for asexual growth, suggest that falcipain 3 is a prime drug target.…”
Section: Discussionmentioning
confidence: 64%
“…It also suggests that the enzyme may serve another purpose in mature schizonts, as the majority of hemoglobin degradation is already complete at schizogony. Both plasmepsin II and falcipain-2 have been shown to cleave host membrane proteins such as band 4.1 and spectrin [16,17]. The significance of these proteolytic events [27] in serum-free RPMI media supplemented with 0.5% Albumax (Gibco BRL, Grand Island, NY), was generated from parasites (3% parasitemia and 2% hematocrit) harvested by saponin lysis at multiple time points during the intraerythrocytic life cycle.…”
mentioning
confidence: 99%